Catalytic Halogen‐Exchange Fluorination of 4‐Chlorobenzaldehyde to 4‐Fluorobenzaldehyde, a Greener Process. Issue 2 (11th January 2022) - Li, Xiukai; Yongcai, Wu; Lijuan, Shi; Zhang, Yugen
Abstract: The direct halogen‐exchange fluorination of 4‐chlorobenzaldehyde was studied under solvent‐free and various diphenyl solvents conditions using spray‐dried KF as a fluorinating agent. Aspects influencing the selectivity and yield of product were investigated in detail, including catalysts and solvents selection, reaction conditions optimization, and side product control. We paid more attention to issues from a perspective of industrial process, such as product separation and catalyst/solvent recycling. The reaction works efficiently with tetraphenyl phosphonium bromide as a phase transfer catalyst under solvent free conditions and in diphenyl solvents. Under the optimum reaction conditions, the yield of 4‐fluorobenzaldehyde reached 90% with a selectivity of 98%. Abstract : The direct halogen‐exchange fluorination of 4‐chlorobenzaldehyde with 90% product yield and 98% product selectivity was achieved under solvent‐free conditions and in diphenyl solvents by using phase transfer catalyst. The system is scalable, the catalyst and solvent are recyclable.